A preliminary account of ARIA‐E in the ongoing open‐label extension phase of BAN2401‐G000‐201 in subjects with early Alzheimer's disease: Human/Human trials: Anti‐amyloid. (7th December 2020) - Swanson, Chad J.; Lai, Robert Y.K.; Bogoslovsky, Tanya; Bradley, Heather; Rabe, Martin; Zhang, Yong; Kramer, Lynn D.
Abstract: Background: Amyloid related imaging abnormalities – edema/effusion (ARIA‐E) are a common finding with some anti‐amyloid antibodies. BAN2401 had an ARIA‐E incidence of 9.9% at the top dose of 10 mg/kg biweekly in the 18‐month Phase 2b study BAN2401‐G000‐201. All subjects with ARIA‐E were immediately discontinued per protocol, regardless of radiologic severity or whether symptoms were noted. Here, we assess preliminary ARIA‐E rates for 10 mg/kg biweekly BAN2401 in the ongoing open label extension (OLE), while exploring the ability to dose through ARIA‐E depending on severity and whether symptoms were observed. Methods: Magnetic resonance imaging (MRI) is conducted to monitor for ARIA‐E at 9wk, 3mo, 6mo, and 12mo over the first 12 months of BAN201 treatment in the OLE. Subjects who experience mild or moderate (severity) radiologic ARIA‐E and are asymptomatic continue dosing per protocol. Dosing is temporarily interrupted in cases of severe (moderate or severe in Japan) and/or symptomatic ARIA‐E and can be resumed up to 2 times upon resolution. Data are based on ongoing reports as of 16 January 2020. Results: A total of 177 subjects from the core study received at least one dose of BAN2401 in the OLE, with 12 cases of ARIA‐E (2 subjects had ARIA‐E in the core) noted across the various core treatment groups during the extension. A total of 167 subjects underwent 9wk MRI, 159 subjects underwent 3mo MRI, 95 subjects underwent 6mo MRI, and 49 subjects reached 9mo of treatment. Among subjects treated with placebo in the core phase, 4/44 subjects had ARIA‐E to date in the OLE. Most events were identified at 9wk or 3mo MRI, and 11/12 cases are in ApoE4 positives. Subjects have continued with dosing in the presence of ARIA‐E in 6/12 cases (1 questionable, 1 mild, 4 moderate), and 5/6 dose‐interrupted cases have resumed dosing to date. Three (3) of the 12 cases were symptomatic, including symptoms of confusion, headache, visual disturbance. ARIA‐E and symptoms resolved in 2 cases, while one case is ongoing. Conclusion: Updated OLE data will be presented and compared to reported rates observed and modelled (Hussein et al, 2019) from the core study.